An Analysis of the Determinants Influencing the Interest of the Muslim Community in Electric Bus Services in Medan City - Indah Wahyu Prastiwi; Muhammad Yafiz; Juliana Nasution (Jurnal Manajemen, 2026)
This investigation elucidates the determinants underpinning the Muslim demographic in Medan City's disposition toward electric bus patronage. Targeted owing to numerical hegemony and alignment with Islamic maslahah paradigms poised to foment sustainable transport ethos amid 2024's subsidized MASTRAN rollout, which evinces tepid uptake despite compliant amenities. Quantitative causal-associative scaffold deployed Likert-scale elicitation (N=100, Slovin-calibrated) and SPSS-orchestrated multivariate regression. Corroborative yields affirm economic, service, and maslahah covariates' salubrious, statistically cogent impress on adoption vector, discretely and conjointly, service paramount. Adjusted R² = 0.578 explicates 57.8% variance, extraneous residuum unaccounted. Corollary imperatives prescribe multifaceted policy praxis, interweaving pecuniary, infrastructural, and axiological strata to catalyze verdant mobility assimilation.